Modeling δD-δ18O Steady-State of Well-Sealed Perennially Ice-Covered Lakes and Their Recharge Source: Examples From Lake Untersee and Lake Vostok, Antarctica - Faucher, Benoit; Lacelle, Denis; Fisher, David A.; Weisleitner, Klemens; Andersen, Dale T. (Frontiers in Earth Science, 2020)
Perennially ice-covered that are tightly sealed from the atmosphere represent a unique group of polar lakes. In these lakes, the δD-δ18O evolution of the water column and its steady-state is controlled by rates of recharge and freezing at the bottom of the ice cover. We developed a recursive model (FREEZCH9) that takes into account the changing salinity in the water column as a result of freezing and mixes the recharge water to the residual water in well-sealed perennially ice-covered lakes. Our model is tested against datasets from Lake Vostok and is used to assess the dD-d18O mass balance of Lake Untersee and evaluate if the lake is in isotopic steady-state. Our FREEZCH9 simulations fit well the predicted dD-d18O values of Lake Vostok and the overlying accreted ice. Simulations with FREEZCH9 also suggests that Lake Untersee is in isotopic steady-state and that its two input sources (i.e. subaqueous terminus melting of the Anuchin glacier and subglacial contributions) have similar dD-d18O composition. Our modeling demonstrates that Lake Untersee most likely did into receive additional input from surface streams during the last 300-500 years. FREEZCH9 may be also used to determine if the hypothetical groundwater systems of the McMurdo Dry Valleys are fully or partially recharged by subglacial lakes.